Epistemological Obstacles on The Quadratic Inequality - Tamba, Kimura Patar; Saragih, Melda Jaya (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
Students often experience difficulties and errors in solving quadratic inequality problems. These difficulties and errors are not only caused by students’ ignorance or misconceptions, but also caused by epistemological obstacles. This study aimed to determine the epistemological obstacles faced by the junior high school students in quadratic inequality. This research was a qualitative research that involved 105 ninth-grade students at one of the junior high schools in Bandung, Indonesia. The data were collected through open-ended tasks and task-based interviews. The data were analyzed using the inductive coding process to classify students’ errors.  The descriptive analysis was carried out to reveal students’ ways of understanding and ways of thinking behind each error to be compared with historical analysis. Based on the description of ways of understanding and ways of thinking and comparison with this historical phenomenon, the epistemological obstacles had be confirmed. The results showed that there were epistemological obstacles in quadratic inequalities. The epistemological obstacles consisted of students' quadratic equation knowledge acts and students' arithmetic knowledge acts. However, no epistemological obstacles were found in the development history of quadratic inequality. Students' epistemological obstacles were parallel to the historical phenomena of quadratic inequality.